“Votive Tablet” and “Heaven” - Raeber, Kuno (Christianity & literature, 2017)
Two poems by Kuno Raeber, and translated by Stuart Friebert, are presented. "VOTIVE TABLET." First Line: From the mouth of the boy the dove; Last Line: in his mother's smiling mouth. "HEAVEN." First Line: The elephants, the whales pant and puff; Last Line: reliquaries remain from the slaughter.